1998
DOI: 10.1115/1.2820691
|View full text |Cite
|
Sign up to set email alerts
|

Flowfield Investigation of the Effect of Rib Open Area Ratio in a Rectangular Duct

Abstract: The spatially periodic turbulent fluid flows and friction in a rectangular passage of width-to-height ratio of 4:1 with perforated rectangular ribs mounted on one wall have been studied using laser Doppler velocimetry and pressure probing. The parameters fixed were rib height to duct hydraulic diameter ratio of 0.106, rib width-to-height ratio of 0.76, rib pitch-to-height ratio of 10, and Reynolds number of 2 × 104, while the main parameter investigated was the rib open-area ratio (β) with values of 0%, 10%, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The results also showed that slit ribs with larger void fractions in a lower flow Reynolds number range provide better thermal performance under a constant friction power constraint. Liou et al [14] focused on the flow characteristics in a channel containing perforated ribs. The fixed parameters were rib height to duct hydraulic diameter ratio of 0.106, rib width to height ratio of 0.76, rib pitch to height ratio of 10 and Reynolds number of 20,000, while the main parameter investigated was the rib open-area ratio with values of 0, 10, 22, 38 and 44 percent.…”
Section: Nomenclaturementioning
confidence: 99%
“…The results also showed that slit ribs with larger void fractions in a lower flow Reynolds number range provide better thermal performance under a constant friction power constraint. Liou et al [14] focused on the flow characteristics in a channel containing perforated ribs. The fixed parameters were rib height to duct hydraulic diameter ratio of 0.106, rib width to height ratio of 0.76, rib pitch to height ratio of 10 and Reynolds number of 20,000, while the main parameter investigated was the rib open-area ratio with values of 0, 10, 22, 38 and 44 percent.…”
Section: Nomenclaturementioning
confidence: 99%
“…Comparing both studies, no Reynolds number dependency of reattachment distance was found. The flow in a straight, rectangular channel with ribs on the two opposite walls was investigated by Liou et al [5,6], and the flow in a rectangular channel with a 180-degree bend was investigated by Schabacker et al [7] and Servouze et al [8]. Iacovides et al [9] conducted a Laser Doppler Anemometry (LDA) investigation of the flow at a Reynolds number of 100,000 in a ribbed channel with a 180-degree turn.…”
Section: Introductionmentioning
confidence: 99%
“…The perforated roughness geometry will yield desired heat transfer augmentation with a minimum friction factor. The effect of the perforated ribs on the heat transfer and friction factor have been studied by several investigators [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%